Reduced graphene oxide triggered epithelial-mesenchymal transition in A549 cells - Liao, Yanyan (Sci Rep, 2018)
Graphene and its derivatives have exhibited wide potential applications in electronics, structural engineering and medicine. However, over utilization and untreated discharge may cause its distribution into environmental as well as biological chain, which raised the concerns of potential health risk as a potential hazard. Accumulating evidence has demonstrated that graphene derivatives induce lung fibrosis in vivo, so overall goal of this study was to explore the molecular mechanisms underlying the pulmonary fibrotic responses of reduced graphene oxide (rGO), using in vitro assays. Epithelial-mesenchymal transition (EMT) has profound effect on development of pulmonary fibrosis. Herein, we evaluated the EMT effect of rGO samples on A549 cells. Firstly, rGO penetrated through the A549 cells membrane into the cytosol by endocytosis and located in late endosome and/or lysosomes observed via transmission electron microscopy (TEM), and were well tolerant by cells. Secondly, rGO promoted the cell migration and invasion capacities at lower doses (below 10 μg/ml), but significantly inhibited the capacities at 20 μg/ml. Moreover, rGO-induced EMT were evidenced by decreased expression of epithelial marker like E-cadherin, β-catenin, Smad4 and increased expression of mesenchymal markers like Vimentin, VEGF-B, TWIST1. Based on our findings, it is supposed that rGO can effectively induce EMT through altering epithelial–mesenchymal transition markers in A549 cells.